Determinant Factors of Fraud in Village Financial Management - Ni Made Madani Hapsari; I Gusti Ayu Nyoman Budiasih; Anak Agung Ngurah Bagus Dwirandra; I Gde Ary Wirajaya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The competence of the apparatus and the internal control system has an effect on fraud but the effect is not always linear because it is suspected that there are contingent factors as mediators, one of which is morality. This study aims to determine the impact of morality mediation on the influence of apparatus competence and internal control on village financial management fraud in Badung Regency. The data in this study are primary data obtained from questionnaires. This type of research is quantitative research. The population in this study were village officials consisting of the village secretary, village treasurer and head of village planning affairs in Badung Regency. The research sample was 138 respondents spread across 46 villages. Data obtained from the results of processing respondents' statements by using a questionnaire. The data were analyzed using the Partial Least Square (PLS) method. Processed using the SmartPLS 3 program. The results of this study indicate that: first, the competence of the apparatus has a significant negative effect on the tendency of fraud in village financial management; second, internal control has a significant negative effect on the tendency of fraud in village financial management; and third, morality mediates the influence of apparatus competence and internal control significantly on the occurrence of fraud in village financial management. The research has implications for the village government and Badung Regency to improve the competence of village apparatus, optimize internal control and develop apparatus morality, in supporting the smooth running of tasks related to village financial management, so that the use of village funds is more targeted.